HUBUNGAN GERAKAN REPETITIF DAN LAMA KERJA DENGAN KELUHAN CARPAL TUNNEL SYNDROME PADA MAHASISWA TEKNIK ARSITEKTUR - Putri Chairun Nissa; Baju Widjasena; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2017)
Carpal Tunnel Syndrome is one kind of cumulative trauma disorders caused by trapped median nerve within the carpal tunnel in the wrist, which is characterized by symptoms of tingling, pain, numbness in the fingers and hands in the area of the median nerve innervation. Students majoring in architectural engineering faculty batch 2013 do task about design structure 4 in 4 semester with average for 8 hours a day and for 3-4 days in a week in front of a computer. From 153 students majoring in architectural engineering faculty, researchers interviewed five respondents had experienced a variety of complaints such as pain, numbness, stiffness, inflammation around the wrist as an impact of using computers. The purpose of this study was to analyze the correlation repetitive motion and work duration with complaints Carpal Tunnel Syndrome in students majoring in architectural engineering faculty batch 2013, Diponegoro University. This study uses a type of observational study with cross sectional approach. The population in this study were entire students majoring in architecture engineering faculty batch 2013 as many as 153 people then taken sample of 59 people use accidental sampling method. Result of chi square test showed that there was no correlation between repetitive motion with the right hand CTS complaints (p-value= 0.593) and left hand (p-value= 0.656) and no correlation between work duration with CTS complaint using the left-hand keyboard (p- value= 0.564) and right-hand mouse (p-value= 0.486). Researchers also suggest that respondents do breaktime and stretching when they feel tired at work.